Post-acute sequelae of COVID-19 and it’s mental health implications - Walia, Namrata; Lat, Jessica; Tariq, Rabeet; Tyagi, Surbhi; Qazi, Adam; Salari, Syeda; Jafar, Amina; Kousar, Tasneem; Bieniek, Sherrie (Journal of Medical Biomedical and Applied Sciences, 2022)
Long COVID or Post-acute sequelae of COVID-19 (PASC) is the term given to persistent symptoms 12 weeks from the initial presentation. Several multi-organ symptoms have been reported by patients. Some common symptoms include headaches, fatigue, memory impairment and mental health complications such as anxiety and depression. People with previous psychiatric diagnosis are at greater risk of developing longer mental health implications from persistent COVID-19 symptoms. Additionally, healthcare workers are at increased risk of being long haulers leading to burnout and exhaustion. A long-termdisease surveillance is required to understand the persistent symptoms or the long-term impact of this infection.